TRADITIONS OF ENGINEERING ACTIVITY AND SUCCESSFUL INNOVATION STRATEGIES OF MODERN GERMANY - Онопрієнко, В. І.; Онопрієнко, М. В. (Proceedings of the National Aviation University Series Philosophy Cultural, 2018)
Germany's innovative strategy, which has deep historical traditions, is effectively incorporated into state policy and the global economy, seeks to give humane and democratic accents to innovative activities.